Engaging medical trainees in resource stewardship through resident-led teaching sessions: a choosing wisely educational initiative - Bal, Chandandeep; Megan, Tesch; Geoffrey, Blair; Olivia, Ostrow; Laila, Premji (Canadian Medical Education Journal, 2020)
Implication statement: Overuse of healthcare resources is prevalent, including among medical trainees. As front-line clinicians and near-peers, residents are well-positioned to teach resource stewardship to medical students and address barriers students may face while trying to “choose wisely.” We describe the implementation of two resident-led, case-based teaching sessions for medical students that focus on resource stewardship. Similar teaching models can be adapted by residents at their own institutions to enhance resource stewardship proficiency amongst trainees.